Multi-scan moving target indication with clutter map and storage solutions - A. S. Solonar; S. A. Gorshkov; P. A. Khmarski; A. M. Vashkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The multi-scan moving target indication with clutter map and storage solutions approach is considered. The estimation performance of compensation devices is compared.